2021
DOI: 10.1002/jmv.27456
|View full text |Cite
|
Sign up to set email alerts
|

Post‐COVID syndrome symptoms, functional disability, and clinical severity phenotypes in hospitalized and nonhospitalized individuals: A cross‐sectional evaluation from a community COVID rehabilitation service

Abstract: There is currently limited information on clinical severity phenotypes of symptoms and functional disability in post-coronavirus disease 2019 (COVID) Syndrome (PCS).A purposive sample of 370 PCS patients from a dedicated community COVID-19 rehabilitation service was assessed using the COVID-19 Yorkshire Rehabilitation Scale where each symptom or functional difficulty was scored on a 0-10 Likert scale and also compared with before infection. Phenotypes based on symptom severity were extracted to identify any no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 21 publications
7
79
1
2
Order By: Relevance
“…7-9 The content was decided using a consensus method and the scale was kept balanced in terms of questions spanning all aspects of the 2001 WHO International Classification of Functioning, Disability and Health (ICF) framework. 10 The content validity of the scale was supported by studies 11, 12 using the scale which revealed symptoms and functional problems similar to other LC studies in the literature. 13, 14…”
Section: Introductionsupporting
confidence: 59%
“…7-9 The content was decided using a consensus method and the scale was kept balanced in terms of questions spanning all aspects of the 2001 WHO International Classification of Functioning, Disability and Health (ICF) framework. 10 The content validity of the scale was supported by studies 11, 12 using the scale which revealed symptoms and functional problems similar to other LC studies in the literature. 13, 14…”
Section: Introductionsupporting
confidence: 59%
“…Preliminary validation data from the COVID-19 Yorkshire Rehabilitation Scale, a condition-specific outcome measure for long COVID, 49 suggest that patients scoring low on one symptom tend to score low on other symptoms too (see figure 2 ) 12 —consistent with severity phenotypes seen in the posthospitalisation COVID-19 study, 10 and suggesting that long COVID may be driven by common mechanisms affecting multiple body systems. Workstream ‘Use the COVID-19 Yorkshire Rehabilitation Scale to monitor symptoms in clinic cohorts’ will test this hypothesis to determine the extent to which the COVID-19 Yorkshire Rehabilitation Scale can be used for triage, targeting interventions and capturing the response to treatments.…”
Section: Methods and Analysismentioning
confidence: 75%
“…A qualitative substudy will seek to understand and address the multiple intersecting inequalities in long COVID service utilisation. 12 Working with and through participating NHS organisations, as well as community and advocacy organisations and selected social media outlets, we will recruit a maximum-variety sample of 30 people with long COVID representing key characteristics of underserved groups who have not (yet) been seen in a long COVID clinic. Sampling criteria include: poverty, homelessness, non-white ethnic groups (including traveller communities) and those with disabilities; within all these groups, we will seek to include a gender balance and recruit diverse age groups.…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations